Faktor-Faktor Yang Berhubungan Dengan Kejadian Hiperemisis Gravidarum Pada Ibu Hamil Di Rsud Kota Depok - Wiwin Nur Fitriani; Rusdiah (Politeknik Karya Husada, 2023)
Background: Hyperemesis gravidarum is a complication of pregnancy which is characterized by excessive nausea and vomiting which causes weight loss and dehydration in pregnant women. The incidence of hyperemesis gravidarum at the Depok City Hospital in 2019 was 69 people and experienced an increase in 2020 as many as 83 people. The purpose: to determine the factors associated with the incidence of hyperemesis gravidarum in pregnant women at Depok City Hospital. Methods: This study used a descriptive research method with a cross-sectional approach, using secondary data. This research was conducted from July to September 2021. The population and sample in this study were all pregnant women who had hyperemesis gravidarum, a total of 83 pregnant women, using the total sempling technique. Data analysis used univariate and bivariate analysis. Results: The results of bivariate analysis showed that parity (p=0.003) and anemia (p=0.038) were associated with hyperemesis gravidarum. The variables age (p= 1.000), education (p= 1000) and occupation (p= 0.498) were not related to the incidence of hyperemesis gravidarum. Conclusion: There is a relationship between parity and anemia with the incidence of hyperemesis gravidarum. With this research it is hoped that it can increase socialization about hyperemesis gravidarum for prevention so that the incidence of hyperemesis gravidarum decreases.